Bi-component micro-nano fiber hydrogel dressing based on conjugate electrospinning technology and preparation method of bi-component micro-nano fiber hydrogel dressing
PSI-NH2/PCL micro-nanofiber hydrogel dressing prepared by conjugated electrospinning technology solves the problems of insufficient liquid absorption, bacterial isolation and mechanical properties of traditional dressings, and achieves efficient wound healing and antibacterial effects. , has excellent mechanical properties and hemostatic properties.
Patent Information
- Application Number
- CN202411316792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-24
AI Technical Summary
Traditional wound dressings have shortcomings in fluid absorption, bacterial insulation and mechanical properties, and are difficult to effectively promote wound healing, especially in hemostatic and antibacterial performance.
Conjugated electrospinning technology is used to prepare two-component micro-nanofiber hydrogel dressings for polysuccinimide (PSI) and polycaprolactone (PCL) and cross-link to form PSI-NH2/PCL micro-nanofibers Hydrogels combine nanofiber structure and hydrogel properties to improve mechanical properties, antibacterial properties and hemostatic properties.
Micronanofiber hydrogel dressing with excellent mechanical properties, strong swelling and liquid absorption capacity, good biocompatibility, and antibacterial rate of more than 99%, can effectively promote wound healing and prevent bacterial infection.
Smart Images

Figure CN119174840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology and a preparation method thereof, which has excellent mechanical, antibacterial and hemostatic properties. Background Art
[0002] The skin is located at the outermost layer of the human body and is extremely vulnerable to damage. After the skin is damaged, subsequent wound infection or severe tissue necrosis may endanger human life, and the repair process involved is also quite complicated. Wound dressings play a vital role in the wound healing process due to their advantages such as low cost, ease of use, and significant effect. However, traditional wound dressings such as cotton gauze and bandages have defects such as easy adhesion, poor fluid absorption capacity, and poor antibacterial effect.
[0003] Hydrogel dressing is a new type of wound dressing with strong liquid absorption and water retention capacity. It can effectively maintain the moist environment of the wound surface and promote wound healing. It has good elasticity and is easy to remove, but lacks multiple biological functions. Electrospun nanofibers can mimic the fiber structure of the natural extracellular matrix (ECM) and provide more sites for cell adhesion and proliferation. Combining electrospun nanofibers with hydrogels can combine the advantages of both, create a microenvironment that promotes wound healing, and improve the performance of the dressing. The ideal wound dressing should also have multiple biological functions and be able to quickly transform the complex pathological microenvironment of the wound site into a microenvironment that promotes healing. Hemostasis is the first stage of wound healing. At this stage, blood vessels contract violently to achieve the purpose of hemostasis. The ideal wound dressing should have an effective hemostatic function. In addition, bacterial infection is an important factor affecting the wound healing process. The healing process involved after skin injury is quite complicated, and the wound surface is susceptible to bacterial infection, which may turn acute wounds into chronic wounds. Therefore, maintaining a sterile microenvironment on the wound surface is crucial for wound dressings.
[0004] Traditional wound dressings such as cotton gauze and bandages are facing huge challenges due to their poor fluid absorption and bacterial isolation. Therefore, it is urgent to design and prepare new wound dressings with suitable structures and multiple biological functions. Therefore, how to make hydrogel dressings have good mechanical properties, swelling and fluid absorption capacity, biocompatibility, and excellent antibacterial and hemostatic properties has become a difficult problem that technicians in the field of biomedical materials need to solve urgently. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, which has excellent mechanical properties, strong swelling and liquid absorption capacity, good biocompatibility, and excellent antibacterial and hemostatic properties, and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, wherein a PSI / PCL micro-nano fiber membrane is prepared by conjugated electrospinning technology from polysuccinimide and polycaprolactone, and the PSI / PCL micro-nano fiber membrane is cross-linked with ethylenediamine to obtain PSI-NH 2 / PCL two-component micro-nanofiber hydrogel dressing.
[0007] The above-mentioned two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, the PSI-NH 2 The fiber diameter of the / PCL two-component micro-nano fiber hydrogel dressing is 1130.2±212.3nm-1294.5±345.2nm, the Young's modulus is 5.1±0.8MPa-33.4±9.2MPa, the breaking strength is 2.3±0.5MPa-7.6±0.6MPa, the breaking elongation is 124.5±18.2%-187.7±92.6%, the swelling rate is 352.4±18.3%-643.8±36.2%, the cell survival rate is 97.8±3.4%-105.3±0.4%, and the antibacterial rate is >99%.
[0008] The above-mentioned two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, the PSI-NH 2 The fiber diameter of the / PCL two-component micro-nano fiber hydrogel dressing is 1187.2±294.1nm, the Young's modulus is 18.1±12.6MPa, the breaking strength is 3.9±0.6MPa, the breaking elongation is 147.3±33.8%, the swelling rate is 536.6±22.6%, the cell survival rate is 103.3±5.0%, and the antibacterial rate is >99%.
[0009] A method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology comprises the following steps:
[0010] 1. Preparation of spinning solution
[0011] (1) Dissolving PSI powder in N,N-dimethylformamide solvent to prepare a PSI spinning solution with a certain mass fraction;
[0012] (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent;
[0013] (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use;
[0014] 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane
[0015] (4) The spinning solutions prepared in step (3) are respectively loaded into medical syringes and spun using a conjugate electrospinning device.
[0016] (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane;
[0017] (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent;
[0018] 3. Cross-linking reaction
[0019] (7) The dried PSI / PCL micro-nanofiber membrane is placed in a sealed container containing ED solution, and ED vapor is used to cross-link PSI to generate PSI-NH 2 / PCL micro-nanofiber hydrogel;
[0020] (8) PSI-NH 2 The / PCL micro-nano fiber hydrogel was dried at 40°C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
[0021] In the above-mentioned method for preparing the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, in the step (1), the mass fraction of the PSI spinning solution is 32%-51%.
[0022] In the above-mentioned method for preparing the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, in the step (2), the mass ratio of PSI to PCL is 80:20-60:40.
[0023] In the above-mentioned method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, in the step (4), the spinning voltage of the conjugated electrospinning is ±10-±15 kV, the drum speed is 100-500 rpm, the distance between the metal spinneret and the drum is 15-20 cm, and the spinning solution flow rate is 0.4-1 mL / h.
[0024] In the above-mentioned method for preparing the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, in step (7), the volume of the ED solution is 1-5 mL, the concentration of ED is 0.1-1 mol / L, and the reaction time is 12-48 h.
[0025] In the above-mentioned method for preparing the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, in the step (1), the PSI powder is dried at 100° C. for 6 hours before preparing the spinning solution.
[0026] In the above-mentioned preparation method of the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, the cross-linking degree between PSI and ED in the PSI-NH2 / PCL micro-nano fiber hydrogel is 50-100%.
[0027] The advantages of the two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology and the preparation method thereof are as follows: the present invention prepares a polysuccinimide (PSI) / polycaprolactone (PCL) nanofiber membrane by conjugated electrospinning technology, and then cross-links it by ethylenediamine (ED) to generate PSI-NH 2 / PCL micro-nano fiber hydrogel dressing. One component, polycaprolactone (PCL), provides excellent mechanical properties, and the other component, polysuccinimide (PSI), is chemically cross-linked with ethylenediamine (ED) to obtain a nanofiber hydrogel that combines the nanofiber structure and hydrogel properties, providing antibacterial and hemostatic properties; PSI cross-linking combines the morphology of nanofibers with the properties of hydrogels, which not only has the advantages of nanofibers mimicking the extracellular matrix (ECM) structure, but also has a high water content, which can effectively absorb exudate from the wound and provide a moist environment. However, PSI-NH 2 The mechanical properties of nanofiber hydrogel dressings are poor, and the addition of PCL significantly improves their mechanical properties. 2 / PCL micro-nano fiber hydrogel dressing has excellent mechanical properties, strong swelling and fluid absorption capacity, good biocompatibility, and excellent antibacterial and hemostatic properties. It can be used as an ideal new wet dressing to promote wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 PSI-NH 2 / Schematic diagram of the preparation process and application of PCL micro-nanofiber hydrogel dressing;
[0029] Figure 2 PSI / PCL micro-nanofibrous membrane and PSI-NH 2 / Surface morphology and structure of PCL micro-nanofiber hydrogel dressing;
[0030] Figure 3 PSI / PCL micro-nanofibrous membrane and PSI-NH 2 FTIR spectrum of / PCL micro-nanofiber hydrogel dressing;
[0031] Figure 4 PSI-NH obtained with different PCL dosages 2 / Mechanical properties of PCL micro-nanofiber hydrogel dressing;
[0032] Figure 5PSI-NH obtained with different PCL dosages 2 Schematic diagram of the swelling and fluid absorption performance of PCL micro-nanofiber hydrogel dressing;
[0033] Figure 6 PSI-NH obtained with different PCL dosages 2 / Test diagram of the antibacterial effect of PCL micro-nano fiber hydrogel dressing on Escherichia coli and Staphylococcus aureus;
[0034] Figure 7 PSI-NH obtained with different PCL dosages 2 / Biocompatibility results of PCL micro-nanofiber hydrogel dressing;
[0035] Figure 8 PSI-NH obtained with different PCL dosages 2 / PCL micro-nanofiber hydrogel dressing hemostatic performance test results. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] In the present invention, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the attached drawings; while "inside" and "outside" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order. The term "plurality" means "two or more".
[0038] like Figure 1 As shown in the figure, a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology is prepared from polysuccinimide and polycaprolactone by conjugated electrospinning technology to obtain PSI / PCL micro-nano fiber membrane, and the PSI / PCL micro-nano fiber membrane is cross-linked with ethylenediamine to obtain PSI-NH 2 / PCL two-component micro-nanofiber hydrogel dressing.
[0039] The preparation method thereof comprises the following steps:
[0040] 1. Preparation of spinning solution
[0041] (1) Dissolving PSI powder in N,N-dimethylformamide solvent to prepare a PSI spinning solution with a certain mass fraction;
[0042] (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent;
[0043] (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use;
[0044] 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane
[0045] (4) The spinning solutions prepared in step (3) are respectively loaded into medical syringes and spun using a conjugate electrospinning device.
[0046] (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane;
[0047] (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent;
[0048] 3. Cross-linking reaction
[0049] (7) The dried PSI / PCL micro-nanofiber membrane is placed in a sealed container containing ED solution, and ED vapor is used to cross-link PSI to generate PSI-NH 2 / PCL micro-nanofiber hydrogel;
[0050] (8) PSI-NH 2 The / PCL micro-nano fiber hydrogel was dried at 40°C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
[0051] The principle of the present invention is that under the action of ethylenediamine vapor, the lactam ring of the polysuccinimide macromolecule opens and generates two new amide bonds with ethylenediamine, thereby realizing cross-linking between the polysuccinimide macromolecules to form a water-insoluble three-dimensional network hydrogel stable structure, and at the same time, increasing the number of amide bonds in the fiber, so that the hydrophilicity of the finally formed hydrogel fiber is significantly improved; in addition, ethylenediamine will generate some amino side chains on the polysuccinimide macromolecule during the cross-linking process, so that the hydrophilicity of the finally formed hydrogel fiber is further improved; on the other hand, the amino group carries a positive charge, which can attract platelets and red blood cells through electrostatic interaction, promote the formation of a large amount of fibrin, and stimulate platelets to release coagulation factors, promote and accelerate blood coagulation, and give the dressing excellent hemostatic function; furthermore, the amino group carries a positive charge and can combine with negatively charged bacteria to achieve the destruction of bacterial cell membranes, causing bacterial death, thereby giving the dressing excellent antibacterial properties and effectively protecting the wound surface from bacterial infection.
[0052] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0053] Example 1
[0054] A two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology comprises the following steps:
[0055] 1. Preparation of spinning solution
[0056] (1) Dry the PSI powder at 100°C for 6 h, dissolve the PSI powder in N,N-dimethylformamide solvent, and prepare a spinning solution with a PSI mass fraction of 32%;
[0057] (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent at a mass ratio of PSI to PCL of 80:20;
[0058] (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use;
[0059] 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane
[0060] (4) The spinning solutions prepared in step (3) were respectively loaded into medical syringes and spun using a conjugate electrospinning device, wherein the spinning voltage was ±10 kV, the drum speed was 100 rpm, the distance between the metal spinneret and the drum was 15 cm, and the spinning solution flow rate was 0.4 mL / h.
[0061] (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane;
[0062] (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent;
[0063] 3. Cross-linking reaction
[0064] (7) The dried PSI / PCL micro-nanofiber membrane was placed in a sealed container containing 1 mol / L ED solution. The volume of the ED solution was 1 mL. The PSI was cross-linked using ED vapor. The reaction time was 12 h. 2 The cross-linking degree between PSI and ED in / PCL micro-nanofiber hydrogel is 50%, generating PSI-NH2 / PCL micro-nanofiber hydrogel;
[0065] (8) PSI-NH 2 The / PCL micro-nano fiber hydrogel was dried at 40°C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
[0066] In this embodiment, the prepared PSI-NH 2The fiber diameter of the / PCL two-component micro-nano fiber hydrogel dressing is 1130.2±212.3nm, the Young's modulus is 5.1±0.8MPa, the breaking strength is 2.3±0.5MPa, the breaking elongation is 187.7±92.6%, the swelling rate is 643.8±36.2%, the cell survival rate is 97.8±3.4%, and the antibacterial rate is >99%.
[0067] Example 2
[0068] A two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology comprises the following steps:
[0069] 1. Preparation of spinning solution
[0070] (1) Dry the PSI powder at 100°C for 6 h, dissolve the PSI powder in N,N-dimethylformamide solvent, and prepare a spinning solution with a PSI mass fraction of 43%;
[0071] (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent at a mass ratio of PSI to PCL of 70:30;
[0072] (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use;
[0073] 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane
[0074] (4) The spinning solutions prepared in step (3) were respectively loaded into medical syringes and spun using a conjugate electrospinning device, wherein the spinning voltage was ±12 kV, the drum speed was 300 rpm, the distance between the metal spinneret and the drum was 17 cm, and the spinning solution flow rate was 0.75 mL / h.
[0075] (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane;
[0076] (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent;
[0077] 3. Cross-linking reaction
[0078] (7) The dried PSI / PCL micro-nanofiber membrane was placed in a sealed container containing 0.25 mol / L ED solution. The volume of the ED solution was 2 mL. ED vapor was used to crosslink PSI. The reaction time was 24 h. 2 The crosslinking degree between PSI and ED in the PCL micro-nanofiber hydrogel is 80%, generating PSI-NH 2 / PCL micro-nanofiber hydrogel;
[0079] (8) PSI-NH 2 The / PCL micro-nano fiber hydrogel was dried at 40°C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
[0080] In this embodiment, the prepared PSI-NH 2 The fiber diameter of the / PCL two-component micro-nano fiber hydrogel dressing is 1187.2±294.1nm, the Young's modulus is 18.1±12.6MPa, the breaking strength is 3.9±0.6MPa, the breaking elongation is 147.3±33.8%, the swelling rate is 536.6±22.6%, the cell survival rate is 103.3±5.0%, and the antibacterial rate is >99%.
[0081] Example 3
[0082] A two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology comprises the following steps:
[0083] 1. Preparation of spinning solution
[0084] (1) Dry the PSI powder at 100°C for 6 h, dissolve the PSI powder in N,N-dimethylformamide solvent, and prepare a spinning solution with a PSI mass fraction of 51%;
[0085] (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent at a mass ratio of PSI to PCL of 60:40;
[0086] (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use;
[0087] 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane
[0088] (4) The spinning solutions prepared in step (3) were respectively loaded into medical syringes and spun using a conjugate electrospinning device, wherein the spinning voltage was ±18 kV, the drum speed was 500 rpm, the distance between the metal spinneret and the drum was 20 cm, and the spinning solution flow rate was 1 mL / h.
[0089] (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane;
[0090] (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent;
[0091] 3. Cross-linking reaction
[0092] (7) The dried PSI / PCL micro-nanofiber membrane was placed in a sealed container containing 0.1 mol / L ED solution. The volume of the ED solution was 5 mL. The PSI was cross-linked using ED vapor. The reaction time was 48 h. 2 The crosslinking degree between PSI and ED in the PCL micro-nanofiber hydrogel is 100%, generating PSI-NH 2 / PCL micro-nanofiber hydrogel;
[0093] (8) PSI-NH 2 The / PCL micro-nano fiber hydrogel was dried at 40°C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
[0094] In this embodiment, the prepared PSI-NH 2 The fiber diameter of the / PCL two-component micro-nano fiber hydrogel dressing is 1294.5±345.2nm, Young's modulus is 33.4±9.2MPa, breaking strength is 7.6±0.6MPa, breaking elongation is 124.5±18.2%, swelling rate is 352.4±18.3%, cell survival rate is 105.3±0.4%, and antibacterial rate is >99%.
[0095] Under the process conditions of Example 2 of the present invention, the performance test results of the two-component micro-nano fiber hydrogel dressing prepared with different PCL ratios are as follows:
[0096] 1. PSI-NH 2 Preparation and morphology analysis of PCL micro-nanofiber hydrogel dressing
[0097] Firstly, PSI / PCL micro-nanofibrous membranes with different ratios were prepared by conjugated electrospinning technology, and then PSI-NH 2 / PCL micro-nano fiber hydrogel dressing. The microscopic morphology and structure were characterized by scanning electron microscopy (SEM, Regulus8100). The sample was cut into small pieces and fixed on the sample stage with conductive glue. Because the sample is not conductive, it needs to be gold-sprayed for 160 seconds. Then, different positions were selected for shooting at different microscopic scales by increasing the magnification. The fibers were randomly selected using Image-J software (National Institutes of Health, USA), the diameters were measured at 100 locations, and the frequency distribution of the diameters was calculated using Origin software.
[0098] Figure 2 PSI / PCL micro-nanofibrous membrane and PSI-NH 2 / PCL micro-nano fiber hydrogel dressing surface morphology and structure diagram. Figure 2 (A) shows the SEM image of the PSI / PCL micro-nano fiber membrane. The spinning solutions with different mass ratios all have good spinning performance. The PSI / PCL-100 / 0 sample is composed of fibers with relatively uniform thickness. The fibers are stacked and distributed in a scattered state without beads. The fibers of the other three groups of samples containing PCL show obvious uneven thickness. Figure 2 (B) shows the average diameter and fiber diameter distribution of PSI fibers and PCL fibers. Quantitative analysis shows that the diameters of PSI fibers in the four groups of samples are not much different. Specifically, the average diameters of PSI fibers in PSI / PCL-100 / 0, PSI / PCL-80 / 20, PSI / PCL-70 / 30, and PSI / PCL-60 / 40 samples are 510.8±56.5nm, 497.8±49.0nm, 510.6±72.1nm, and 503.7±60.7nm, respectively. In addition, the diameters of PCL fibers in the three groups of samples PSI / PCL-80 / 20, PSI / PCL-70 / 30, and PSI / PCL-60 / 40 increased significantly with the increase of PCL content, and the average diameters were 609.6±57.0nm, 885.9±95.4nm, and 1084.7±196.8nm, respectively.
[0099] PSI-NH 2 SEM morphology of / PCL micro-nanofiber hydrogel dressing Figure 2 As shown in (C), the nanofiber hydrogel after ED cross-linking can basically maintain the original fiber morphology, with uniform thickness, smoothness, no beads, and slight adhesion, indicating that cross-linking through ED will not significantly affect the original microscopic morphology of the nanofibers. Figure 2 (D) shows PSI-NH 2 The average fiber diameter and fiber diameter distribution of PSI / PCL, combined with quantitative analysis, showed that the diameter of nanofibers after ED crosslinking increased significantly. 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 The average fiber diameters of / PCL-60 / 40 were 1015.5±254.5nm, 1175.8±224.8nm, 1187.2±294.1nm and 1272.1±331.7nm, respectively. This is because the ED cross-linking process enhances the interaction between PSI molecular chains, forms cross-linking points inside the fiber structure, increases the density and structural stability of the fiber, and thus increases the PSI-NH 2The diameter of the fiber.
[0100] 2. PSI-NH 2 FTIR spectral analysis of / PCL micro-nanofiber hydrogel dressing
[0101] The present invention uses a Fourier transform infrared spectrometer (TENSOR27, Germany) to characterize the characteristic functional groups of different PSI / PCL micro-nano fiber membranes and PSI-NH2 / PCL micro-nano fiber hydrogel dressings.
[0102] like Figure 3 A shows the FTIR spectrum of PSI / PCL micro-nanofiber membrane before cross-linking. Figure 3 As shown in A, the four groups of PSI / PCL nanofibers all showed characteristic peaks related to PSI, namely, at a wavelength of 1703 cm -1 and 1794cm -1 The two characteristic absorption peaks at 2949 cm-1 are attributed to the coupling effect of the asymmetric stretching of two adjacent carbonyl groups on the PSI chain. -1 There is a characteristic peak at 2 Compared with the PSI / PCL-100 / 0 sample, the PSI / PCL-80 / 20, PSI / PCL-70 / 30, and PSI / PCL-60 / 40 samples all have a peak at 1659 cm -1 、1256cm -1 、1397cm -1 There are obvious characteristic peaks at the bottom, which represent the C=O stretching vibration absorption peak, CO stretching vibration absorption peak, CH 2 Bending vibration absorption peaks, these characteristic peaks are all attributed to PCL polymer, which indicates that the PSI / PCL micro-nano fiber membrane was successfully prepared. In addition, there is no obvious offset between the characteristic peaks in the figure, and no new characteristic peaks are observed. The surface PSI and PCL are only simply physically mixed, and no chemical reaction occurs.
[0103] like Figure 3 B shows the cross-linked PSI-NH 2 FTIR spectrum of PCL micro-nanofiber hydrogel dressing. After ED cross-linking, the 1794 cm -1 and 1703cm -1 The characteristic peak at 3297 cm -1 There is a characteristic peak at 1639cm -1 A characteristic peak was observed at , which was the stretching vibration peak of C=O in the amide bond, which confirmed that a cross-linking reaction occurred between PSI to generate PSI-NH2 / PCL micro-nanofiber hydrogel dressing. 2 Compared with the PSI-NH / PCL-100 / 0 sample, 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30, PSI-NH 2 / PCL-60 / 40 samples are all at 1162cm -1 、1253cm -1 、1726cm -1 、2930cm -1 Obvious characteristic peaks appeared at 1162 cm -1 、1253cm -1 、2930cm -1 The CO stretching vibration absorption peak is at 1726 cm -1 The C=O stretching vibration absorption peak is represented by .
[0104] 3. PSI-NH 2 / PCL micro-nanofiber hydrogel dressing has excellent mechanical properties
[0105] PSI-NH was measured by a universal material testing machine (Instron 5965, USA). 2 / PCL micro-nanofiber hydrogel dressing tensile mechanical properties. The samples were cut into 10mm×30mm rectangular strips, and the thickness of each sample was first recorded with a thickness gauge, and then clamped into a tensile testing machine. The clamping distance at both ends of each sample was 10mm, the stretching distance was set to 10mm, the stretching speed was 10mm / min, and the test was repeated 5 times to obtain the stress-strain curve, and the Young's modulus, breaking strength and breaking elongation were further calculated.
[0106] in, Figure 4 A is the tensile stress-strain curve. The mechanical test results show that with the increase of PCL content, the breaking strength and Young's modulus of PSI-NH2 / PCL micro-nanofiber hydrogel dressing increase significantly. Figure 4 B, PSI-NH 2 The Young's modulus of / PCL-100 / 0 (4.2±0.9MPa) is significantly lower than that of PSI-NH 2 / PCL-80 / 20(5.6±1.2MPa),PSI-NH 2 / PCL-70 / 30 (18.1±12.6MPa) and PSI-NH 2 / PCL-60 / 40(31.9±8.9MPa).PSI-NH 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 / The breaking strength of PCL-60 / 40 is as follows Figure 4 C, which are 1.3±0.3MPa, 2.9±0.6MPa, 3.9±0.6MPa and 7.4±0.4MPa respectively. 2 / PCL-100 / 0, PSI-NH 2 The Young's modulus and breaking strength of the PSI-NH / PCL-60 / 40 nanofiber hydrogel dressing increased by 659.5% and 469.2%, respectively. 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 / The elongation at break of PCL-60 / 40 is as follows Figure 4 D, which are 100.0±30.6%, 184.0±90.1%, 147.3±33.8% and 128.7±20.1%, respectively. The significant increase in Young's modulus and breaking strength of the three groups of PCL-containing samples can be attributed to the mechanical enhancement effect of PCL, which indicates that the addition of PCL can significantly improve the PSI-NH 2 Mechanical strength of PCL micro-nanofiber hydrogel dressing.
[0107] 4. PSI-NH 2 / PCL micro-nano fiber hydrogel dressing has strong fluid absorption
[0108] The ideal wound dressing should not only provide a moist environment, but also have good fluid absorption capacity to absorb exudate from the wound. 2 The morphological changes of PCL / PCL micro-nanofiber hydrogel dressings in contact with safranin dye solution characterize the wicking capacity of different dressings. Figure 5 As shown in A, there are four groups of PSI-NH 2 / Actual photo of the wicking process of PCL micro-nano fiber hydrogel dressing. When the sample first came into contact with the dye solution, the liquid quickly penetrated into the dressing and began to diffuse. From the photo taken 2 minutes after the liquid was absorbed, it can be observed that as the PCL content increases, the wicking effect of the nanofiber hydrogel dressing tends to decrease. Figure 5B is the swelling rate curve. Quantitative analysis shows that the nanofiber hydrogel dressings with different mass ratios all exhibit good water absorption and swelling properties. Within a certain period of time, the swelling rate of the hydrogel increases with the extension of the immersion time, and basically reaches swelling equilibrium within 15 minutes. Specifically, PSI-NH 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 The final swelling ratios of PSI-NH4+ / -PCL-60 / 40 were 912.5±47.1%, 639.1±32.5%, 536.6±22.6% and 362.2±19.5%, respectively, indicating that the swelling ratio of the hydrogel dressing decreased with the increase of PCL content, because PCL is a hydrophobic polymer without hydrophilic groups. 2 The / PCL-60 / 40 sample also exhibited a higher swelling ratio, greater than 350%, which was attributed to the typical hydrogel properties of the dressing.
[0109] 5. PSI-NH 2 / PCL micro-nanofiber hydrogel dressing has excellent antibacterial properties
[0110] After skin damage, long-term exposure of the wound will increase the possibility of microbial infection, thereby slowing down the healing process. An ideal wound dressing should have excellent antibacterial properties and be able to maintain a sterile environment at the wound site to promote wound healing. This example uses the oscillation method and the viable bacteria count method to test 4 different PSI-NH 2 / The antibacterial ability of PCL micro-nanofiber hydrogel dressing against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive), such as Figure 6 As shown in the following table:
[0111]
[0112]
[0113] From the table, we can see that PSI-NH 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2The antibacterial rates of / PCL-60 / 40 nanofiber hydrogel dressing against Escherichia coli and Staphylococcus aureus were both greater than 99%, showing excellent antibacterial properties. The antibacterial mechanism of the nanofiber hydrogel dressing is mainly that PSI is cross-linked to generate amino PSI. The amino groups on its molecular chain carry positive charges on the polymer surface, but the bacterial surface generally carries negative charges. Therefore, the amino groups on the dressing can destroy the bacterial cell membrane by combining with the anionic part of the bacteria, causing bacterial death. Experiments have shown that pure PSI-NH 2 Nanofiber hydrogel dressings already have good antibacterial ability, and after adding PCL, they still show excellent antibacterial properties, indicating that PSI-NH 2 / PCL micro-nanofiber hydrogel can be used as wound dressing to effectively protect the wound from bacterial infection.
[0114] 6. PSI-NH 2 / PCL micro-nano fiber hydrogel dressing has good biocompatibility
[0115] In the process of wound healing, cell survival and proliferation are crucial for the regeneration of damaged skin tissue, so an ideal wound dressing should have good biocompatibility. In this example, human dermal fibroblasts (HDFs) were used to test PSI-NH 2 The biocompatibility of the PCL micro-nanofiber hydrogel dressing was investigated. HDFs were seeded in a 96-well plate, and the culture medium was replaced with four different PSI-NH 2 / PCL micro-nanofiber hydrogel dressing extract. After 3 days of culture, Calcein-AM dye and PI dye were used to dye live cells green and dead cells red, respectively, and then the morphology and growth of cells were observed using a fluorescence microscope. Figure 7 As shown in the live-dead cell staining fluorescence image of A, all sample groups showed excellent cell activity, and almost no dead cells (red) were observed. The proliferation of HDFs after 3 days of culture was determined by the MTT method, and the cell survival rate was calculated. Figure 7 B is the test graph of HDFs cell survival rate after three days of culture. It can be seen from the figure that the control group, PSI-NH 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 The cell viabilities of PSI-NH40 / PCL-60 / 40 were 100±1.6%, 100.0±3.5%, 98.8±3.6%, 104.4±0.3% and 103.3±5.0%, respectively. These results indicate that the four different PSI-NH40 2 / PCL micro-nanofiber hydrogel dressings have excellent biocompatibility and are non-cytotoxic to HDFs.
[0116] 7. PSI-NH 2 / PCL micro-nanofiber hydrogel dressing has excellent hemostatic properties
[0117] Hemostasis is the first stage of wound healing. Wound dressings need to be in direct contact with the wound during the wound repair process, and the hemostatic function of wound dressings can accelerate wound healing. The hemostatic process mainly relies on blood coagulation, platelet aggregation and fibrin network. PSI-NH was evaluated by in vivo mouse liver bleeding model 2 / PCL micro-nanofiber hydrogel dressing. Figure 8 A shows the hemostasis process. Since the mice in the control group did not receive any treatment after the liver was punctured, the bleeding was the most serious. 2 The amount of liver bleeding in mice treated with / PCL micro-nanofiber hydrogel dressing was significantly reduced. Figure 8 The SEM images of blood cell adhesion shown in B show the adhesion of platelets and red blood cells on the four dressing samples, indicating that the four different PSI-NH 2 / PCL micro-nano fiber hydrogel dressings can enrich blood cells and enhance the hemostatic effect. The amount of bleeding in the damaged liver of mice after 60s is as follows Figure 8 As shown in C, control group, PSI-NH 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30 and PSI-NH 2 The bleeding volume of PSI-NH / PCL-60 / 40 after 60s was 159.4±17.7mg, 15.3±0.6mg, 44.6±6.7mg, 26.6±6.2mg, and 45.0±13.0mg, respectively. The bleeding volume of the control group after 60s was significantly higher than that of the other four dressing sample groups, and there was no significant difference among the four sample groups. 2 / PCL-100 / 0, PSI-NH 2 / PCL-80 / 20, PSI-NH 2 / PCL-70 / 30, PSI-NH 2 / PCL-60 / 40 reduced the bleeding volume by 90.4%, 72.0%, 83.3%, and 71.8% after 60s, respectively. These results indicate that pure PSI-NH 2 Hydrogel dressings have good hemostatic effects due to their excellent structure and are expected to become ideal wound dressing materials.2 The excellent hemostatic performance of / PCL micro-nanofiber hydrogel dressing can be attributed to two main factors. On the one hand, the hydrogel dressing has excellent swelling performance and liquid absorption capacity, which can effectively absorb wound blood and closely adhere to the wound surface. On the other hand, PSI-NH 2 The amino groups in the polymer carry a positive charge and can attract platelets and red blood cells through electrostatic interactions, promoting the formation of large amounts of fibrin, while stimulating platelets to release coagulation factors, promoting and accelerating blood coagulation.
[0118] Among various biomaterials, polysuccinimide (PSI) has good biodegradability and biocompatibility, excellent antibacterial properties after cross-linking, and it is easy to combine with ECM proteins and growth factors to promote cell proliferation. However, hydrogel materials based on PSI exhibit poor mechanical properties. The ideal wound dressing should have sufficient mechanical strength and a certain degree of flexibility, and be able to withstand complex biological mechanical forces. Polycaprolactone (PCL) is a semi-crystalline polymer widely used in the field of wound treatment. It has excellent biodegradability and biocompatibility as well as good mechanical properties and structural stability. It can be used as a medical material with high requirements for mechanical strength, and can also be combined with other biomaterials to improve its performance. However, PCL exhibits high hydrophobicity and lacks the ability to promote cell adhesion. The present invention combines PSI with PCL, which overcomes the shortcomings of poor mechanical properties of single-component PSI and poor biological activity of PCL, and at the same time can give play to the advantages of each of the two components to obtain a composite material with excellent comprehensive performance. The two-component nanofiber hydrogel dressing of the present invention has excellent mechanical properties, strong swelling and liquid absorption capacity, good biocompatibility, and also has excellent antibacterial and hemostatic properties, and can be used as an ideal new wet dressing to achieve the purpose of promoting wound healing.
[0119] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.
Claims
1. A two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology, characterized in that: PSI / PCL micro-nano fiber membrane was prepared from polysuccinimide and polycaprolactone by conjugated electrospinning technology, and the PSI / PCL micro-nano fiber membrane was cross-linked with ethylenediamine to obtain PSI-NH2 / PCL two-component micro-nano fiber hydrogel dressing.
2. The two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 1 is characterized in that: The fiber diameter of the PSI-NH2 / PCL two-component micro-nano fiber hydrogel dressing is 1130.2±212.3nm-1294.5±345.2nm, the Young's modulus is 5.1±0.8MPa-33.4±9.2MPa, the breaking strength is 2.3±0.5MPa-7.6±0.6MPa, the breaking elongation is 124.5±18.2%-187.7±92.6%, the swelling rate is 352.4±18.3%-643.8±36.2%, the cell survival rate is 97.8±3.4%-105.3±0.4%, and the antibacterial rate is >99%.
3. The two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 1 is characterized in that: The fiber diameter of the PSI-NH2 / PCL two-component micro-nano fiber hydrogel dressing is 1187.2±294.1 nm, the Young's modulus is 18.1±12.6 MPa, the breaking strength is 3.9±0.6 MPa, the breaking elongation is 147.3±33.8%, the swelling rate is 536.6±22.6%, the cell survival rate is 103.3±5.0%, and the antibacterial rate is >99%.
4. A method for preparing the two-component micro-nano fiber hydrogel dressing according to any one of claims 1 to 3, characterized in that: The steps include:
1. Preparation of spinning solution (1) Dissolving PSI powder in N,N-dimethylformamide solvent to prepare a PSI spinning solution with a certain mass fraction; (2) Determine the mass of PCL based on the mass of PSI, and dissolve PCL particles in hexafluoroisopropanol solvent; (3) Stir the two solutions together at room temperature to obtain a spinning solution for later use; 2. Preparation of PSI / PCL Micro-Nano Fiber Membrane (4) The spinning solutions prepared in step (3) are respectively loaded into medical syringes and spun using a conjugate electrospinning device. (5) Control the spinning time according to the required thickness to obtain the PSI / PCL micro-nano fiber membrane; (6) Place the PSI / PCL micro-nanofiber membrane in a vacuum drying oven and further dry it at room temperature for 24 h to remove the residual solvent; 3. Cross-linking reaction (7) placing the dried PSI / PCL micro-nano fiber membrane in a sealed container containing ED solution, and using ED vapor to cross-link PSI to generate PSI-NH2 / PCL micro-nano fiber hydrogel; (8) The PSI-NH2 / PCL micro-nano fiber hydrogel was dried at 40 °C for 24 h to remove the residual ED and obtain a two-component micro-nano fiber hydrogel dressing.
5. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: In the step (1), the mass fraction of the PSI spinning solution is 32%-51%.
6. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: In the step (2), the mass ratio of PSI to PCL is 80:20-60:
40.
7. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: In the step (4), the spinning voltage of the conjugate electrospinning is ±10-±15 kV, the drum speed is 100-500 rpm, the distance between the metal spinneret and the drum is 15-20 cm, and the spinning solution flow rate is 0.4-1 mL / h.
8. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: In the step (7), the volume of the ED solution is 1-5 mL, the concentration of ED is 0.1-1 mol / L, and the reaction time is 12-48 h.
9. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: In the step (1), the PSI powder is dried at 100° C. for 6 hours before preparing the spinning solution.
10. The method for preparing a two-component micro-nano fiber hydrogel dressing based on conjugated electrospinning technology according to claim 4, characterized in that: The cross-linking degree between PSI and ED in the PSI-NH2 / PCL micro-nano fiber hydrogel is 50-100%.
Citation Information
Cited By
Piezoelectric dressing as well as preparation method and application thereof
CN121360270A
